How to start a home-based jewelry making business - Loughran, Maire (Guilford, Ct : Globe Pequot Press, 2009)
Turn your passion into profit, develop a smart business plan, set market-appropriate prices, profit from craft fairs and trade shows, sell to local and national retail shops, make money on the internet.
So you want to start your own jewerly making business -- From dreams to reality: defining your jewelry making business -- Setting up your office and workshop -- The business plan: your plan of action -- Getting started -- Financial planning -- Financial management -- Taxes and recordkeeping -- Jewelry making legal and ethical issues -- Marketing your jewelry -- How to make the internet and e-commerce work for your business -- Take your jewelry making business to the next level -- Jewelry making training and certification.
Includes bibliographical references and index.
Keywords: Jewelry making; Selling -- Jewelry